Pollen Viability and Pollen Tube Growth of IPB’s Papaya - Ketty Suketi; Cenra Intan Hartuti Tuharea; Winarso Dradjad Widodo; Roedhy Poerwanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The purpose of the research was to examine the pollen germination process and growth rate of pollen tubes of papaya. Pollen tube growth of nine genotypes of papaya (IPB 1, IPB 2, IPB 3, IPB 4, IPB 5, IPB 7, IPB 8, IPB 9, and IPB 10) was investigated in this experiment in order to study their pollen germination rate and pollen viability. The fresh pollen were excised from the fl owers of papaya grown at Tajur Field Station of Research Center for Tropical Fruit, Bogor Agricultural University (IPB), Bogor. The extracted pollen was cultured aseptically on the Brewbaker and Kwack medium (pH 7.3) at ambient temperature of 26-28 °C. Pollen germination and pollen tube growth was observed under optical microscope with 100 and 400 magnifi cation. Papaya pollen viability was not associated with size-based categories of papaya fruits. IPB 4 had the longest pollen tube at fi rst 30 minutes after germination (115.5 µm), whereas IPB 10 had the shortest (99.5 µm). The distance from stigma to ovary in hermaphrodite fl owers varies with genotypes, ranging from 7.38 to 13.44 mm. Average length of pollen tube within four hours of germination for small papaya fruit category (IPB 1, IPB 3, and IPB 4) was 1,030.67 ± 19.14 μm, while the distance between stigma and ovary was short (14.85 ± 2.19 mm) so that the expected of fertilization process occurred sooner. At the end of the experiment (four hours after germination), IPB 1 genotype had the longest pollen tube (1,052 µm) while IPB 9 genotype (913 µm) had the shortest pollen tube. Genotype with the highest percentage of germination at the end experiment was IPB 2 (65.65%), whereas the lowest was IPB 7 (42.56%).